PERANCANGAN MEDIA KOMIK GENG BAGALUIK - WENDRI GUSTI NANDA, Drs. Syafwan, M.Si., Drs. Mediagus, M.Pd. (Universitas Negeri Padang, 2017)
This thesis aims to inform teenage gangs conditions to public education in the media, especially the world of comics. Embodiments of the comics media because they are freer to imagine and fantasize. Methods and steps in the process begins with the preparation, elaboration, synthesis, the realization of the concept will be presented to the public through exhibitions. This work provides information to the public about juvenile gangs standpoint, the problems disclosed in the comics discusses the condition of juvenile gangs and how to react to it.Kata Kunci: Geng Remaja, Komik, Edukasi